Living textiles. (22nd December 2023) - Scott, Jane
Abstract : Abstract : Living textiles are evolving at the interface of textiles and biology. This emerging field proposes methods to design with, by, and for the growth of microorganisms using textiles thinking, textile materials and textile process. Textiles transform the microscale of fibres and biosynthesised polymers into high performance, environmentally responsive systems that function at a macroscale through the hierarchical structuring of constituent materials. As biotechnology looks for scalable solutions for diverse applications in the built environment and beyond, textiles offer a variety of strategies for bio-assembly and bio-fabrication.